2021
DOI: 10.21203/rs.3.rs-131195/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serological Assessment of COVID-19 Patients in Brazil: Levels, Avidity, and Subclasses of IgG Against RBD

Abstract: SARS-CoV-2 is considered a global emergency, resulting in an exacerbated crisis in the health public in the world. Although there are advances in vaccine development, it is still not available for many countries. On the other hand, an immunological response that mediates protective immunity or indicates that predict disease outcome in SARS-CoV-2 infection remains undefined. This work aimed to assess the antibody levels, avidity, and subclasses of IgG to RBD protein, in symptomatic patients with severe and mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…Even within 1 year after the onset of clinical symptoms, the vast majority of COVID‐19 outpatients in our study did not develop high avidity IgG toward SARS‐CoV‐2 NP, and 68% of the patients showed no high avidity IgG toward SARS‐CoV‐2 RBD. These findings of incomplete avidity maturation after natural infection with SARS‐CoV‐2 are in line with the findings by several other groups 9,10,17–20 . Also, the study by Luo et al 24 is indirectly confirming this view, as Luo et al used 3 M urea.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Even within 1 year after the onset of clinical symptoms, the vast majority of COVID‐19 outpatients in our study did not develop high avidity IgG toward SARS‐CoV‐2 NP, and 68% of the patients showed no high avidity IgG toward SARS‐CoV‐2 RBD. These findings of incomplete avidity maturation after natural infection with SARS‐CoV‐2 are in line with the findings by several other groups 9,10,17–20 . Also, the study by Luo et al 24 is indirectly confirming this view, as Luo et al used 3 M urea.…”
Section: Discussionsupporting
confidence: 89%
“…An initial analysis revealed that avidity maturation after SARS‐CoV‐2 infection remained at an untypical low level in most cases 12 . This is in line with the reports by other groups 9,10,17–20 …”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…A different study that enrolled IIER patients confirmed the result. 19 In COVID-19, obesity increases the chance of the patient being hospitalized in intensive care units, it is usually associated with other aggravating factors, like hypertension and diabetes; and has been related to immunological impairments, like increased inflammation and decrease of Treg activity, which may contribute to inadequate immune response. 20 This information highlights the need to observe comorbidities in the risk assessment of COVID-19 patients.…”
Section: S1 S2 and N Iga And Igg Against Sars-cov-2mentioning
confidence: 99%